Biodegradable film packaging material and preparation method thereof
By adopting a self-assembled multi-layer structure in the film packaging material, combining starch, nano zinc oxide and modified polymers, the problems of slow degradation speed and insufficient antibacterial performance of existing biodegradable films are solved, efficient barrier, antioxidant and antibacterial properties are achieved, and rapid degradation in the natural environment is achieved, reducing environmental impact.
Patent Information
- Application Number
- CN202411807073.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
The existing biodegradable films have slow degradation speed and insufficient antibacterial performance, making it difficult to meet the needs of rapid degradation and food safety.
The self-assembled film packaging material is used, including a film matrix and assembly layer, which consists of starch, nano zinc oxide and PBAT, and the assembly layer consists of modified chitosan and modified polyvinyl alcohol, which enhances barrier, antioxidant and antibacterial properties through multi-layer design.
It significantly improves the barrier properties between oxygen and water vapor, enhances tensile and optical properties, and achieves rapid biodegradation, reduces environmental impact, and meets the requirements of sustainable development.
Smart Images

Figure BDA0005179538510000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of film packaging materials, and in particular to a biodegradable film packaging material and a preparation method thereof. Background Art
[0002] At present, the traditional plastic films widely used in the packaging industry are not easy to degrade, exist in the natural environment for a long time, pollute the soil and water sources, and have a negative impact on the ecological environment. Therefore, the development of an environmentally friendly and biodegradable packaging film has become an important research direction in the current field of packaging materials. In today's society, the development of the packaging industry is closely related to people's lives. Traditional plastic films are widely used in the packaging of food, medicine, electronic products and other fields due to their lightness, durability and high cost-effectiveness. However, while this widely used traditional plastic film brings great convenience to our lives, it also brings environmental problems that cannot be ignored. As we all know, traditional plastic films are mainly made of petroleum-based polymers such as polyethylene and polypropylene. These materials have extremely high chemical stability, which makes them extremely difficult to degrade in the natural environment. As a result, these films are often discarded at will after completing their packaging function, and then exist in the natural environment for a long time. This long-standing plastic waste not only damages the soil structure, affects the air permeability and water retention capacity of the soil, but also penetrates into the water source, pollutes groundwater and rivers, and threatens the aquatic ecosystem. In addition, animals accidentally eating these plastic wastes will cause casualties and further destroy the ecological balance. Therefore, biodegradable films make great contributions to protecting the environment.
[0003] However, although the existing biodegradable films can meet environmental protection requirements to a certain extent, they still have the following problems: the degradation rate is slow and it is difficult to meet the demand for rapid degradation; the antibacterial performance is not safe enough, especially in the field of food packaging, it is difficult to ensure the safety of food. Summary of the invention
[0004] The purpose of the present invention is to provide a biodegradable film packaging material and a preparation method thereof, which effectively enhances the barrier properties of oxygen and water vapor, and also improves the tensile properties and optical properties, while achieving rapid biodegradation.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions:
[0006] A biodegradable film packaging material, characterized in that it includes a film substrate and assembly layers arranged on both sides of the film substrate, wherein the film substrate includes the following raw materials in mass fractions: 10-15% starch, 0.10-0.15% nano zinc oxide and the remainder PBAT, and the assembly layers include an outer modified chitosan layer and an inner modified polyvinyl alcohol layer, and the assembly layers are stacked in 5-8 layers.
[0007] Preferably, the starch is food-grade corn starch with an amylose content of 27 to 33%.
[0008] Preferably, the specific preparation method of the modified chitosan material is as follows: weigh acrylamide and add it to a strong alkaline solution, freeze it for 1 to 2 hours until it becomes a paste, stir it evenly and freeze it for a second time for 12 to 14 hours, take it out and thaw it at room temperature, stir it again and put it in a freezer and freeze it for 12 to 14 hours, cycle freezing and thawing for 2 more times, pour the paste mixture into a three-necked flask, place it in a low-temperature thermostatic bath at a temperature of 15°C, add a certain amount of chitosan and react for 24 to 36 hours, after the reaction is completed, adjust the pH of the mixture to neutral with a 7% hydrochloric acid solution and a 7% sodium hydroxide solution, vacuum filter to remove undissolved acrylamide and impurities, put the filtrate into a dialysis membrane and dialyze it in deionized water for 7 days, during which the deionized water is replaced every 24 hours, and after the dialysis is completed, the chitosan acrylamide aqueous solution is rotary evaporated to remove a large amount of water to obtain the modified chitosan material.
[0009] Preferably, the strong alkaline solution is prepared by mixing lithium hydroxide, potassium hydroxide and urea in mass fractions of 4.5%, 7% and 8% respectively with the remainder being deionized water.
[0010] Preferably, the specific preparation method of the modified polyvinyl alcohol is as follows: add polyvinyl alcohol powder to deionized water, stir at room temperature for 15 minutes to fully swell it, then heat to 98 ° C and continue stirring for 1 hour until the polyvinyl alcohol is completely dissolved into a uniform and transparent solution, cool to room temperature and ultrasonicate for 15 minutes, as solution A, add EGCG to a 2% glacial acetic acid aqueous solution, continue stirring until it is completely dissolved, as solution B, then pour solution A into solution B and stir slowly, mix evenly, ultrasonicate the mixed liquid for 15 minutes to remove bubbles, and finally obtain a modified polyvinyl alcohol solution.
[0011] Preferably, the mass fraction of the polyvinyl alcohol powder in the solution A is 5-8%, the mass fraction of EGCG in the solution B is 1-5%, and the catechin content in the EGCG is 56-72 mg / g.
[0012] A method for preparing a biodegradable film packaging material, characterized in that it comprises the following steps:
[0013] Starch and PBAT are placed in a vacuum drying oven to remove moisture, and then mixed with nano zinc oxide according to a mass fraction ratio, and then the mixed base material is slowly added to an extruder to prepare a mixed masterbatch, and then cast to obtain a film matrix;
[0014] The modified chitosan material is dissolved in a 1% glacial acetic acid solution to obtain a modified chitosan material solution, and a film substrate is deposited in the modified chitosan material solution for 5 to 8 minutes. After the film is taken out, it is washed twice in deionized water, each time for 1 to 2 minutes, and air-dried for 3 minutes; then the base film is deposited in a modified polyvinyl alcohol solution for 5 to 8 minutes, and a cycle is completed through the same washing and drying process. The above cycle is repeated 5 to 8 times to complete the deposition assembly of the required number of layers to obtain a biodegradable film packaging material.
[0015] Preferably, the temperature settings of zones 1 to 7 of the extrusion device are: 150°C, 155°C, 160°C, 165°C, 165°C, 160°C, 155°C, respectively, and the rotation speed is 40 to 50 r / min.
[0016] Preferably, the blast drying conditions are: temperature of 30° C. and relative humidity less than 45% RH.
[0017] In summary, the present invention realizes a composite structure of multilayer materials on the surface of the PBAT substrate by self-assembly, which can effectively enhance the barrier properties of oxygen and water vapor, and the tensile properties and optical properties are also improved. The modified polyvinyl alcohol layer achieves good antioxidant, antibacterial activity and anti-proliferation properties through EGCG, and the modified chitosan layer assembled with multilayer intervals has excellent mechanical properties. At the same time, the multilayer design can have a certain self-healing ability. In addition, the decomposition rate in the natural environment is significantly improved. It can not only degrade quickly after use, but also minimize the impact on the environment throughout its life cycle, which meets the requirements of sustainable development. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with specific implementations thereof, but these embodiments do not constitute a limitation to the present invention.
[0019] Example 1
[0020] A biodegradable film packaging material comprises a film substrate and assembly layers arranged on both sides of the film substrate, wherein the film substrate comprises the following raw materials in mass fractions: 10% starch, 0.15% nano zinc oxide and the remainder PBAT, the assembly layers comprise an outer modified chitosan layer and an inner modified polyvinyl alcohol layer, the assembly layers are stacked with 5 layers in total, and the starch adopts food-grade corn starch with an amylose content of 27-33%.
[0021] The specific preparation method of the modified chitosan material is as follows: weigh acrylamide and add it to a strong alkaline solution, freeze it for 1 hour until it becomes a paste, stir it evenly and freeze it for a second time for 12 hours, take it out and thaw it at room temperature, stir it again and put it in a freezer and freeze it for 12 hours, cycle freezing and thawing for 2 more times, pour the paste mixture into a three-necked flask, place it in a low-temperature thermostatic bath at a temperature of 15°C, add a certain amount of chitosan and react for 24 hours, after the reaction is completed, adjust the pH of the mixture to neutral with a 7% by mass hydrochloric acid solution and a 7% by mass sodium hydroxide solution, vacuum filter to remove undissolved acrylamide and impurities, put the filtrate into a dialysis membrane and dialyze it in deionized water for 7 days, during which the deionized water is replaced every 24 hours, and after the dialysis is completed, the chitosan acrylamide aqueous solution is rotary evaporated to remove a large amount of water to obtain the modified chitosan material.
[0022] The strong alkaline solution is prepared by mixing lithium hydroxide, potassium hydroxide and urea in mass fractions of 4.5%, 7% and 8% respectively and the balance of deionized water.
[0023] The specific preparation method of modified polyvinyl alcohol is as follows: add polyvinyl alcohol powder to deionized water, stir at room temperature for 15 minutes to fully swell it, then heat to 98°C and continue stirring for 1 hour until the polyvinyl alcohol is completely dissolved into a uniform and transparent solution, cool to room temperature and then ultrasonicate for 15 minutes as solution A, add EGCG to a 2% glacial acetic acid aqueous solution, continue stirring until it is completely dissolved as solution B, then pour solution A into solution B and stir slowly, mix evenly, ultrasonicate the mixed liquid for 15 minutes to remove bubbles, and finally obtain a modified polyvinyl alcohol solution.
[0024] The mass fraction of polyvinyl alcohol powder in solution A is 5%, the mass fraction of EGCG in solution B is 1%, and the catechin content in EGCG is 56-72 mg / g.
[0025] A method for preparing a biodegradable film packaging material comprises the following steps:
[0026] Starch and PBAT are placed in a vacuum drying oven to remove moisture, and then mixed with nano zinc oxide according to a mass fraction ratio, and then the mixed base material is slowly added to an extruder. The temperature settings of zones 1 to 7 of the extruder are: 150°C, 155°C, 160°C, 165°C, 165°C, 160°C, 155°C, and the rotation speed is 40r / min, thereby preparing a mixed masterbatch, which is then cast to obtain a film matrix;
[0027] The modified chitosan material is dissolved in a 1% glacial acetic acid solution to obtain a modified chitosan material solution, and a film substrate is deposited in the modified chitosan material solution for 5 minutes. After the film is taken out, it is washed twice in deionized water, each time for 1 minute, and then air-dried for 3 minutes at a temperature of 30°C and a relative humidity of less than 45% RH. The base film is then deposited in a modified polyvinyl alcohol solution for 5 minutes, and a cycle is completed through the same washing and drying process. The above cycle is repeated 5 times to complete the deposition assembly of the required number of layers to obtain a biodegradable film packaging material.
[0028] Example 2
[0029] A biodegradable film packaging material comprises a film substrate and assembly layers arranged on both sides of the film substrate, wherein the film substrate comprises the following raw materials in mass fractions: 12% starch, 0.12% nano zinc oxide and the remainder PBAT, the assembly layers comprise an outer modified chitosan layer and an inner modified polyvinyl alcohol layer, the assembly layers are stacked with 7 layers in total, and the starch adopts food-grade corn starch with an amylose content of 27-33%.
[0030] The specific preparation method of the modified chitosan material is as follows: weigh acrylamide and add it to a strong alkaline solution, freeze it for 2 hours until it becomes a paste, stir it evenly and freeze it for a second time for 13 hours, take it out and thaw it at room temperature, stir it again and freeze it in a freezer for 13 hours, cycle freezing and thawing for 2 more times, pour the paste mixture into a three-necked flask, place it in a low-temperature constant temperature bath at a temperature of 15°C, add a certain amount of chitosan and react for 30 hours, after the reaction is completed, adjust the pH of the mixture to neutral with a 7% by mass hydrochloric acid solution and a 7% by mass sodium hydroxide solution, vacuum filter to remove undissolved acrylamide and impurities, put the filtrate into a dialysis membrane and dialyze it in deionized water for 7 days, during which the deionized water is replaced every 24 hours, and after the dialysis is completed, the chitosan acrylamide aqueous solution is rotary evaporated to remove a large amount of water to obtain the modified chitosan material.
[0031] The strong alkaline solution is prepared by mixing lithium hydroxide, potassium hydroxide and urea in mass fractions of 4.5%, 7% and 8% respectively and the balance of deionized water.
[0032] The specific preparation method of modified polyvinyl alcohol is as follows: add polyvinyl alcohol powder to deionized water, stir at room temperature for 15 minutes to fully swell it, then heat to 98°C and continue stirring for 1 hour until the polyvinyl alcohol is completely dissolved into a uniform and transparent solution, cool to room temperature and then ultrasonicate for 15 minutes as solution A, add EGCG to a 2% glacial acetic acid aqueous solution, continue stirring until it is completely dissolved as solution B, then pour solution A into solution B and stir slowly, mix evenly, ultrasonicate the mixed liquid for 15 minutes to remove bubbles, and finally obtain a modified polyvinyl alcohol solution.
[0033] The mass fraction of polyvinyl alcohol powder in solution A is 6%, the mass fraction of EGCG in solution B is 3%, and the catechin content in EGCG is 56-72 mg / g.
[0034] A method for preparing a biodegradable film packaging material comprises the following steps:
[0035] Starch and PBAT are placed in a vacuum drying oven to remove moisture, and then mixed with nano zinc oxide according to a mass fraction ratio, and then the mixed base material is slowly added to an extruder. The temperature settings of zones 1 to 7 of the extruder are: 150°C, 155°C, 160°C, 165°C, 165°C, 160°C, 155°C, and the rotation speed is 40 to 50 r / min, thereby preparing a mixed masterbatch, which is then cast to obtain a film matrix;
[0036] The modified chitosan material is dissolved in a 1% glacial acetic acid solution to obtain a modified chitosan material solution, and the film substrate is deposited in the modified chitosan material solution for 6 minutes. After the film is taken out, it is washed twice in deionized water, each time for 1 minute, and then air-dried for 3 minutes at a temperature of 30°C and a relative humidity of less than 45%RH. The base film is then deposited in a modified polyvinyl alcohol solution for 6 minutes, and a cycle is completed through the same washing and drying process. The above cycle is repeated 7 times to complete the deposition assembly of the required number of layers to obtain a biodegradable film packaging material.
[0037] Example 3
[0038] A biodegradable film packaging material comprises a film substrate and assembly layers arranged on both sides of the film substrate, wherein the film substrate comprises the following raw materials in mass fractions: 15% starch, 0.15% nano zinc oxide and the remainder PBAT, the assembly layers comprise an outer modified chitosan layer and an inner modified polyvinyl alcohol layer, the assembly layers are stacked with 8 layers in total, and the starch adopts food-grade corn starch with an amylose content of 27-33%.
[0039] The specific preparation method of the modified chitosan material is as follows: weigh acrylamide and add it to a strong alkaline solution, freeze it for 2 hours until it becomes a paste, stir it evenly and freeze it for a second time for 14 hours, take it out and thaw it at room temperature, stir it again and put it in a freezer and freeze it for 14 hours, cycle freezing and thawing for 2 more times, pour the paste mixture into a three-necked flask, place it in a low-temperature thermostatic bath at a temperature of 15°C, add a certain amount of chitosan and react for 36 hours, after the reaction is completed, adjust the pH of the mixture to neutral with a 7% by mass hydrochloric acid solution and a 7% by mass sodium hydroxide solution, vacuum filter to remove undissolved acrylamide and impurities, put the filtrate into a dialysis membrane and dialyze it in deionized water for 7 days, during which the deionized water is replaced every 24 hours, and after the dialysis is completed, the chitosan acrylamide aqueous solution is rotary evaporated to remove a large amount of water to obtain the modified chitosan material.
[0040] The strong alkaline solution is prepared by mixing lithium hydroxide, potassium hydroxide and urea in mass fractions of 4.5%, 7% and 8% respectively and the balance of deionized water.
[0041] The specific preparation method of modified polyvinyl alcohol is as follows: add polyvinyl alcohol powder to deionized water, stir at room temperature for 15 minutes to fully swell it, then heat to 98°C and continue stirring for 1 hour until the polyvinyl alcohol is completely dissolved into a uniform and transparent solution, cool to room temperature and then ultrasonicate for 15 minutes as solution A, add EGCG to a 2% glacial acetic acid aqueous solution, continue stirring until it is completely dissolved as solution B, then pour solution A into solution B and stir slowly, mix evenly, ultrasonicate the mixed liquid for 15 minutes to remove bubbles, and finally obtain a modified polyvinyl alcohol solution.
[0042] The mass fraction of polyvinyl alcohol powder in solution A is 8%, the mass fraction of EGCG in solution B is 5%, and the catechin content in EGCG is 56-72 mg / g.
[0043] A method for preparing a biodegradable film packaging material comprises the following steps:
[0044] Starch and PBAT are placed in a vacuum drying oven to remove moisture, and then mixed with nano zinc oxide according to a mass fraction ratio, and then the mixed base material is slowly added to an extruder. The temperature settings of zones 1 to 7 of the extruder are: 150°C, 155°C, 160°C, 165°C, 165°C, 160°C, 155°C, and the rotation speed is 40 to 50 r / min, thereby preparing a mixed masterbatch, which is then cast to obtain a film matrix;
[0045] The modified chitosan material is dissolved in a 1% glacial acetic acid solution to obtain a modified chitosan material solution, and a film substrate is deposited in the modified chitosan material solution for 8 minutes. After the film is taken out, it is washed twice in deionized water for 2 minutes each time, and then air-dried for 3 minutes at a temperature of 30°C and a relative humidity of less than 45% RH; then the base film is deposited in a modified polyvinyl alcohol solution for 8 minutes, and a cycle is completed through the same washing and drying process. The above cycle is repeated 8 times to complete the deposition and assembly of the required number of layers to obtain a biodegradable film packaging material.
[0046] The biodegradable film packaging materials prepared in Examples 1 to 3 were compared with the film packaging materials prepared only by PBAT as Comparative Example 1 for tensile strength and elongation at break test performance. In addition, according to GB / T19811-2005, a simulated soil burial degradation experiment was carried out to detect the weight loss rate at different times. The test results are shown in Table 1.
[0047] Table 1 Performance test results
[0048]
[0049] It can be seen from the data in Table 1 that the biodegradable film packaging material prepared by the present invention is significantly superior to ordinary PBAT film materials in terms of tensile strength and elongation at break, as well as in the soil burial degradation experiment. The present invention realizes a composite structure of multilayer materials on the surface of the PBAT substrate by self-assembly, which can effectively enhance the barrier properties of oxygen and water vapor, and the tensile properties and optical properties are also improved. The modified polyvinyl alcohol layer achieves good antioxidant, antibacterial activity and anti-proliferation properties through EGCG, and the modified chitosan layer assembled with multilayer intervals has excellent mechanical properties. At the same time, the multilayer design can have a certain self-healing ability. In addition, the decomposition rate in the natural environment is significantly improved, which can not only degrade quickly after use, but also minimize the impact on the environment throughout its life cycle, meeting the requirements of sustainable development.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions should also be deemed to fall within the protection scope of the technical solution of the present invention.
Claims
1. A biodegradable film packaging material, characterized in that: It includes a film substrate and assembly layers arranged on both sides of the film substrate, wherein the film substrate includes the following raw materials in mass fractions: 10-15% starch, 0.10-0.15% nano zinc oxide and the remainder PBAT, and the assembly layers include an outer modified chitosan layer and an inner modified polyvinyl alcohol layer, and the assembly layers are stacked in 5-8 layers.
2. The biodegradable film packaging material according to claim 1, characterized in that: The starch is food-grade corn starch with an amylose content of 27-33%.
3. The biodegradable film packaging material according to claim 1, characterized in that: The specific preparation method of the modified chitosan material is as follows: weigh acrylamide and add it to a strong alkaline solution, freeze it for 1-2 hours until it becomes a paste, stir it evenly and freeze it for a second time for 12-14 hours, take it out and thaw it at room temperature, stir it again and put it in a freezer and freeze it for 12-14 hours, cycle freezing and thawing for two more times, pour the paste mixture into a three-necked flask, place it in a low-temperature thermostatic bath at a temperature of 15° C., add a certain amount of chitosan and react for 24-36 hours, after the reaction is completed, adjust the pH of the mixture to neutral with a 7% by mass hydrochloric acid solution and a 7% by mass sodium hydroxide solution, remove undissolved acrylamide and impurities by vacuum filtration, put the filtrate into a dialysis membrane and dialyze it in deionized water for 7 days, during which the deionized water is replaced every 24 hours, and after the dialysis is completed, the chitosan acrylamide aqueous solution is rotary evaporated to remove a large amount of water to obtain the modified chitosan material.
4. The biodegradable film packaging material according to claim 3, characterized in that: The strong alkaline solution is prepared by mixing lithium hydroxide, potassium hydroxide and urea in mass fractions of 4.5%, 7% and 8% respectively with the remainder of deionized water.
5. The biodegradable film packaging material according to claim 1, characterized in that: The specific preparation method of the modified polyvinyl alcohol is as follows: polyvinyl alcohol powder is added to deionized water, first stirred at room temperature for 15 minutes to fully swell it, then heated to 98°C and stirred continuously for 1 hour until the polyvinyl alcohol is completely dissolved into a uniform and transparent solution, cooled to room temperature and ultrasonicated for 15 minutes, as solution A, EGCG is added to a 2% glacial acetic acid aqueous solution, and continued to be stirred until it is completely dissolved, as solution B, then solution A is poured into solution B and slowly stirred, after mixing evenly, the mixed liquid is ultrasonicated for 15 minutes to remove bubbles, and finally a modified polyvinyl alcohol solution is obtained.
6. The biodegradable film packaging material according to claim 5, characterized in that: The mass fraction of the polyvinyl alcohol powder in the solution A is 5-8%, the mass fraction of EGCG in the solution B is 1-5%, and the catechin content in the EGCG is 56-72 mg / g.
7. A method for preparing a biodegradable film packaging material, characterized in that: The steps include: Starch and PBAT are placed in a vacuum drying oven to remove moisture, and then mixed with nano zinc oxide according to a mass fraction ratio, and then the mixed base material is slowly added to an extruder to prepare a mixed masterbatch, and then cast to obtain a film matrix; The modified chitosan material was dissolved in 1% glacial acetic acid solution to obtain a modified chitosan material solution, and the film substrate was deposited in the modified chitosan material solution for 5-8 minutes. After the film was taken out, it was washed twice in deionized water, each time for 1-2 minutes, and then dried by air for 3 minutes; The base film is then deposited in a modified polyvinyl alcohol solution for 5 to 8 minutes, and undergoes the same cleaning and drying process to complete a cycle. The above cycle is repeated 5 to 8 times to complete the deposition and assembly of the required number of layers to obtain a biodegradable film packaging material.
8. The method for preparing a biodegradable film packaging material according to claim 7, characterized in that: The temperature settings of zones 1 to 7 of the extrusion device are 150° C., 155° C., 160° C., 165° C., 165° C., 160° C., and 155° C., respectively, and the rotation speed is 40 to 50 r / min.
9. The method for preparing a biodegradable film packaging material according to claim 7, characterized in that: The blast drying conditions are: temperature of 30° C. and relative humidity less than 45% RH.
Citation Information
Patent Citations
Degradable food packaging film with antibacterial function
CN108276598A
Nano-zinc oxide reinforced cassava starch / PBAT degradable material and preparation method thereof
CN109401229A
Green biodegradable plastic film and processing technology thereof
CN109929228A
Water-blocking enhanced degradable antibacterial film as well as preparation method and application thereof
CN113667168A
Preparation method of organic-inorganic composite material film
CN116622104A